Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.119
|View full text |Cite
|
Sign up to set email alerts
|

Pricing for Online Resource Allocation: Intervals and Paths

Abstract: We present pricing mechanisms for several online resource allocation problems which obtain tight or nearly tight approximations to social welfare. In our settings, buyers arrive online and purchase bundles of items; buyers' values for the bundles are drawn from known distributions. This problem is closely related to the so-called prophet-inequality of Krengel and Sucheston [22] and its extensions in recent literature. Motivated by applications to cloud economics, we consider two kinds of buyer preferences. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the graph G induced by constraints (2), two agents are adjacent if their intervals overlap. For an agent t, any agents t ′ < t with I t ′ ∩ I t = ∅ must have I t ′ contain the point ℓ t , since ℓ t ′ ≤ ℓ t and the intervals are contiguous.…”
Section: Our Results In Relation To Previous Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the graph G induced by constraints (2), two agents are adjacent if their intervals overlap. For an agent t, any agents t ′ < t with I t ′ ∩ I t = ∅ must have I t ′ contain the point ℓ t , since ℓ t ′ ≤ ℓ t and the intervals are contiguous.…”
Section: Our Results In Relation To Previous Resultsmentioning
confidence: 99%
“…Our paper is most related to the existing work involving matroids [11,6,5] and XOS valuation functions [8,5]. We should mention that interval-scheduling constraints have also been studied in [10,2], where it is shown that with no assumptions on the intervals, the guarantee relative to the prophet is at most O(log log L/ log L), where L is the length of (number of items in) the longest interval. That is, with no assumptions on the intervals, a constant-factor is impossible.…”
Section: Other Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Dütting et al [10,11] provided a general framework for posted-price mechanisms in Bayesian settings. Chawla et al [6] showed that static, anonymous bundle pricing mechanisms are useful when buyers' preferences have complementarities. Ezra et al [15] provided upper and lower bounds on the largest fraction of the optimal social welfare that can be guaranteed with static prices for several classes of valuations, such as submodular, XOS, or subadditive.…”
Section: :4 Market Pricing For Matroid Rank Valuationsmentioning
confidence: 99%
“…Interest in prophet inequalities has surged recently, in part due to applications in pricing and auction design driven by the observation that the fixed threshold can be viewed as a posted price. This has lead to a line of literature studying prophet inequalities for more general instances of the allocation problem, yielding approximatelyoptimal online policies and incentive compatible auctions for increasingly general problem instances with many objects and rich classes of valuation functions (e.g., [4], [5], [6], [7], [8], [9], [10], [11], [12]).…”
Section: Introductionmentioning
confidence: 99%